When movement disorders hurt: Addressing pain in hyperkinetic disorders. (November 2017) - Relja, Maja; Miletić, Vladimir
Abstract: Pain is an important nonmotor symptom in movement disorders. Dystonia is a hyperkinetic movement disorder characterized by involuntary, sustained or intermittent muscle contractions causing abnormal movements, postures or both. Contrary to common views the nonmotor symptoms are present in dystonia patients. Pain is a prevailing feature of cervical dystonia (CD), the most common form of focal dystonia. The mechanism of pain in CD remains mostly unknown, but there are growing evidence that it could not be only the consequence of muscle hyperactivity. We have shown that botulinum toxin (BoNT) produced pain relief before muscle relaxation and that effect on pain relief lasted longer than the effect on motor improvement. More and more data suggest that pain relief could be attributed to the direct effect of BoNT type A on central nervous system. Pain, depression, and anxiety have been shown to be significant determinants of QoL in focal dystonia patients. Routine clinical examination in patients with dystonia should include evaluation of motor as well as non-motor symptoms. Selective rating assessment should be used in clinical practice to quantify pain. Specific assessment of pain is important to determine the effect of BoNT as the most effective treatment in focal dystonia. Highlights: Non-motor symptoms are increasingly recognised in patients with dystonia. Pain is a prevailing non-motor feature in patients with CD and significant determinant of QoL. Clinical examination in patients with dystonia should include evaluation of motor as well as non-motor symptoms. Treatment with BoNT significantly reduces pain. Thera are growing evidence on central mechanism of BoNT induced pain relief.